The Invisible Workers: Capturing Home-based Work in India. Issue 2 (December 2019) - Samantroy, Ellina
The present paper is contextualised within the backdrop of high informality and a declining female labour force participation in India. Women in India are predominantly in the informal sector engaged in various kinds of precarious employment including home based work that remains unaccounted and undercounted in National Accounting Statistics. Since the home based workers are not into a formal employment relationship and mostly work within the domains of the household, they largely remain outside the purview of social protection. The present paper provides an insight into home based work in India and tries to locate home based workers and their employment conditions vis a vis their location in various social groups. It also tries to understand the existing data gaps in capturing home based workers thereby attempting to locate the gender concerns in data sources for providing full visibility to the informal economy. The paper tries to provide policy recommendations for addressing the concerns associated with home-based workers and larger questions on reducing gendered vulnerabilities across social groups for a sustained labour market participation. The paper is based on secondary data from several governmental sources including the Census, National Sample Survey (NSS), Time Use Survey 1998–99 and the Economic Census.